PENGARUH PIJAT TUI NA TERHADAP PENINGKATAN NAFSU MAKAN BALITA - Tamara, Hesti; Kamidah, Kamidah (Cahaya Ilmu Bangsa Institute, 2024)
ABSTRACT Reduced appetite in toddlers is a psychological disorder that affects the growth and development process. If this condition is not treated immediately, complications can occur, including poor nutrition in toddlers and motor disorders in children. WHO data shows that 7.7% of children under five are malnourished and 15% are underweight. The 2019 Indonesian Health Profile data for under-five children with malnutrition was 3.9% and the percentage of malnutrition reached 13.8%. Tui Na massage works by improving blood circulation in the spleen and digestion and increasing the child's appetite. Objective: To find out whether there is an effect of Tui Na massage on increasing toddlers' appetite. Method: Using pre experimental design, one group pretest-posttest approach. Sample of 32 toddlers with poor appetite. The sampling technique uses random sampling. Analysis test using Wilcoxon Results: Shows that the average appetite of toddlers before the Tui Na massage is 3.09, the lowest appetite score is 1, the highest appetite score is 5, and the mode value is 4 which means less. The average appetite of toddlers after the Tui Na massage was 6.53, the lowest appetite score was 4, the highest appetite score was 10, and the mode score was 6, which means good. The analysis test shows that Asymp.Sig (2-tailed) 0.000 <0.05. Conclusion: There is an effect of Tui Na massage on increasing toddlers' appetite. Keywords: Appetite, tui na, toddlers ABSTRAK Nafsu makan berkurang pada balita adalah gangguan psikologis yang mempengaruhi proses tumbuh kembang. Kondisi ini jika tidak segera ditangani dapat terjadi komplikasi diantaranya balita dengan gizi buruk dan gangguan motorik pada anak. WHO menunjukkan balita gizi buruk 7,7% dan Underweight 15%. Data profil Kesehatan Indonesia 2019 balita gizi buruk sebesar 3,9% dan persentase gizi kurang mencapai 13,8%. Pijat Tui Na bekerja dengan memperlancar peredaran darah di limpa dan pencernaan dan membuat nafsu makan anak meningkat. Tujuan: Mengetahui adakah pengaruh pijat Tui Na terhadap peningkatan nafsu makan balita. Metode : Menggunakan pre exsperimental design, pendekatan one group pretest- posttest. Sampel 32 balita dengan nafsu makan kurang. Teknik pengambilan sampel menggunakan random sampling. Uji analisa menggunakan Wilcoxon Hasil : Menunjukkan rata-rata nafsu makan balita sebelum pijat Tui Na sebesar 3.09, skor nafsu makan terendah adalah 1, skor nafsu makan tertinggi 5, dan nilai modus yaitu 4 yang artinya kurang. Rata-rata nafsu makan balita sesudah pijat Tui Na sebesar 6.53, skor nafsu makan terendah 4, skor nafsu makan tertinggi 10, dan nilai modus yaitu 6 yang artinya baik. Uji analisis diketahui Asymp.Sig (2-tailed) 0.000 <0.05. Kesimpulan :Ada pengaruh pijat Tui Na terhadap peningkatan nafsu makan balita. Kata Kunci : Balita, nafsu makan, pijat tui na